Waris Anak Angkat dalam Perspektif Hukum Islam - Nur Ana Fitriyani (Isti`dal : Jurnal Studi Hukum Islam, 2020)
This study aims to determine the distribution of inheritance to adopted children in Petekeyan Village and to find out how Islamic law reviews in Indonesia regarding the distribution of inheritance to adopted children in Petekeyan Village. In analyzing the data, the authors used qualitative analysis, namely the analysis of the discussion around the implementation of inheritance for adopted children in Petekeyan village.The point of view used as an approach in the preparation of this thesis is a case study approach. A case study is a research strategy in which the researcher carefully investigates a program, event, activity, process, or group of individuals. The results of this study indicate that based on the results of research, adoption in Petekeyan village does not break the kinship relationship between adopted children and their biological parents and adopted children are also included in the kinship of adoptive parents. Adopted children in Petekeyan village still inherit from their adoptive parents as well as their biological parents. The right to inherit an adopted child against the inheritance of his adoptive parents, namely if the heir does not have biological children, it will be determined by his immediate family or other heirs by looking at the things that have been carried out by the adopted child towards his obligations to his adoptive parents. However, if the heir has biological children, it will be determined by deliberation between the adopted child and the biological child. Adoption of children in Petekeyan village is the same as adopting children in society in general, which can be taken from within the family itself or from outside the family. Inheritance that is carried out in Petekeyan village in general is the giving of inheritance directly from the heir to his heirs while the heir is still alive, in other words, giving inheritance by way of a grant. Penelitian ini bertujuan untuk mengetahui pembagian harta waris terhadap anak angkat di Desa Petekeyan dan untuk mengetahui bagaimana tinjauan hukum Islam di Indonesia mengenai pembagian harta waris terhadap anak angkat di desa Petekeyan. Dalam menganalisis data, penyusun menggunakan  analisis kualitatif,  yakni  analisis  pada pembahasan  sekitar pelaksanaan waris  terhadap anak   angkat   di   desa   Petekeyan.  Sudut  pandang   yang   digunakan   sebagai pendekatan dalam penyusunan skripsi ini adalah pendekatan studi kasus. Studi kasus merupakan strategi penelitian di mana di dalamnya peneliti menyelidiki secara cermat suatu program, peristiwa, aktivitas, proses, atau sekelompok individu. Hasil  penelitian  ini menunjukkan  bahwa berdasarkan  hasil penelitian  pengangkatan anak  di  desa Petekeyan  tidak  memutuskan  hubungan kekerabatan antara anak angkat dengan orang tua kandungnya dan anak angkat juga termasuk dalam kekerabatan orang tua angkatnya. Anak angkat di desa Petekeyan   tetap   mewarisi   dari  orang  tua   angkatnya   dan   juga  orang   tua kandungnya. Hak mewarisi anak angkat terhadap harta warisan orang tua angkatnya yaitu jika pewaris tidak mempunyai anak kandung, maka akan ditentukan oleh keluarga dekat atau ahli waris lain dengan melihat hal-hal yang telah dilaksanakan oleh anak angkat terhadap kewajiban-kewajibannya terhadap orang tua angkatnya. Namun jika pewaris memiliki anak kandung maka akan  ditentukan dengan musyawarah antara anak angkat dan anak kandung. Pengangkatan anak di desa Petekeyan sama halnya dengan pengangkatan anak pada  masyarakat  pada  umumnya,  yaitu  bisa diambil  dari  kalangan  keluarga sendiri maupun dari luar keluarga. Pewarisan yang dilakukan di desa Petekeyan pada umumnya  yaitu  pemberian  harta  warisan  secara  langsung  dari pewaris kepada ahli warisnya saat pewaris masih hidup, dengan kata lain pemberian warisan dengan cara hibah.